PENERAPAN EWOM UNTUK PENENTUAN KEPUTUSAN PEMBELIAN BARANG VIRTUAL GAME ONLINE (STUDI KASUS : WILAYAH JAWA BARAT) - Yunika Komalasari; Dewi Sulastriningsih; Marjito Marjito (STMIK Mardira Indonesia, Bandung, 2019)
In the current era of globalization, information technology is advancing rapidly. Related to the online game industry. This is exploited by online game developers to benefit from this industry. One way to do virtual product marketing is by the electronic method of word of mouth (EWOM). The purpose of this study was to study the EWOM dimensions of purchasing decisions of virtual goods in online games. The research instrument discusses the questionnaire and uses a Likert scale as the Score score. By conducting descriptive tests, validity, reliability, classic assumptions and multiple linear regression, hypothesized against 100 respondents. The results of this study are known as the Intensity variable which has a positive relationship with Virtual Goods Purchasing Decisions in Online Games with a relationship rate of 7.84%. Opinion Validity Variables have a positive relationship with Virtual Goods Purchasing Decisions in Online Games with a relationship level of 6.60%. Content Variable has a positive relationship to the Purchase Decision of Virtual Goods in Online Games with a relationship level of 41.73%. And the variables Intensity, Opinion Opinion, and Content are positively related to the Purchase Decision of Virtual Goods in Online Games with a relationship level of 64.8%. Keyword : EWOM, Comments Column, Frequency of Use, Positive Comments, Recommendations, Information, Purchase DecisionsDOI : http://doi.org/10.5281/zenodo.3631053